Prehypertension and hypertension prevalence and risk factors among adult population in Republic of Serbia: A cross-sectional study - Šipetić-Grujičić Sandra; Miljuš Dragan; Soldatović Ivan; Nikolić Aleksandra; Vujčić Isidora (Vojnosanitetski Pregled)
Background/Aim. Prehypertension and hypertension are an important public health problem worldwide and although they can be modified, they are often a risk for cardiovascular diseases. The aim of this study was to determine the prevalence of prehypertension and hypertension and associated risk factors in the adult population (15+ years) of Serbia. Methods. The cross-sectional study covered 14,623 adult respondents, but 14,422 volunteered to measure their blood pressure according to a pre-defined protocol. A stratified two-stage national representative random sampling approach was used for the selection of the survey sample. Results. In 2013, 17.7% of Serbian population, aged 15 and over, was normotensive, every third (33.1%) person had prehypertension, and every second (49.3%) had hypertension. The standardized prevalence of prehypertension and hypertension was 40.6% and 34.5%, respectively; 57.8% of the hypertensive population were receiving medical treatment. Among those receiving medical treatment, 35.2% (36.4% males and 33.2% females) had a blood pressure within the normal range. According to the results of multivariate logistic regression analysis, independently significant risk factors for hypertension compared to persons with normotension were older age (50 and more) (p < 0.001), overweight (p < 0.001) and obesity (p < 0.001), moderate (p < 0.001) and large (p < 0.001) waist circumference in both sexes, and nonurban place of residence in females (p = 0.006). In females, independently significant risk factors for prehypertension compared to persons with normotension were older age (50 and more) (p < 0.001), overweight (p < 0.001) and obesity (p < 0.001), moderate (p < 0.001) and large (p < 0.001) waist circumference, but high level of physical activity was significantly protective (p = 0.014). In males, overweight (p < 0.001) and obesity (p < 0.001) were independently significant risk factors for prehypertension. Conclusion. Serbia belongs to countries with a high prevalence of prehypertension and hypertension. Our results emphasize the need for a new public health strategy for the prevention, detection and treatment of prehypertension and hypertension. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 175042]